Optimization of a heating pattern for single grain (Y,er)Ba2Cu3O7−x by infiltration growth process - Kamarudin, Aliah Nursyahirah; Miryala, Muralidhar; Awang Kechik, Mohd Mustafa; Chen, Soo Kien; Lim, Kean Pah; Abdul Karim, Muhammad Khalis; Shabdin, Muhammad Kashfi; Shaari, Abdul Halim (Elsevier, 2024)
In this study, the fabrication of single grain bulks (Y,Er)Ba2Cu3O7−x “(Y,Er)−123” superconductors is well studied to enhance high superconducting performance in the mixed binary system between yttrium and erbium elements. A series of isothermal experiments of mixed (Y,Er)2BaCuO5 “(Y,Er)−211” binary system has been prepared at various constant temperatures for 50 hours to optimize the heating pattern to produce large-sized (Y,Er)−123 bulks single domain. (Y,Er)−123 bulks were fabricated using the infiltration growth (IG) process. All samples obtained were studied by X-ray diffraction (XRD), Scanning electron microscope (SEM), Superconducting quantum interference device (SQUID), and trapped field measurements. In isothermal experiments, it revealed that the optimum temperature obtained to grow a good (Y,Er)−123 bulks was at 985 °C. All samples showed Tc-onset from 89 K to 91 K indicating all samples show superconducting nature. Microstructural analysis indicated that the presence of non-superconducting (Y,Er)−211 fine particles within the (Y,Er)−123 matrix improved the Jc values up to 41.60 kA/cm2. On the other hand, slow cooling bulk (Y,Er)−123 has been conducted after obtaining the optimum growth temperature window from the isothermal experiment. (Y,Er)−123 bulks were fabricated using a slow cooling IG process. It revealed that the homogenous distribution of (Y,Er)−211 particles in the (Y,Er)−123 matrix improved the superconducting performance, Jc, and trapped field. As a result, Jc obtained for a single domain of (Y,Er)−123 bulk was 43.03 kA/cm2 at 77 K, H//c-axis and self-field.